Utilization E-Commerce and Tax Understanding of MSME Taxpayer Compliance in Palu City - Imelda, Imelda; Totanan, Chalarce; Parwati, Ni Made Suwitri (Universitas KH. Abdul Chalim Mojokerto, 2026)
The development of digital technology has encouraged MSMEs to shift toward e-commerce based marketing to enhance business effectiveness and expand market reach. This transformation also affects potential tax revenues, prompting the government to revise the MSME taxation mechanism through the implementation of a 0.5% Final Income Tax rate. However, tax compliance among MSMEs remains low, largely due to limited tax literacy and understanding. This study aims to analyze the influence of e-commerce utilization and tax understanding on the tax compliance of MSMEs in Palu City. The research involved 344 respondents and employed multiple linear regression analysis. The results indicate that e-commerce utilization has no effect on tax compliance, whereas tax understanding has a positive and significant influence. Theoretically, these findings reinforce that tax understanding is a dominant factor in shaping compliance behavior. Practically, the results highlight the need to improve tax literacy and strengthen the integration of taxation systems with e-commerce platforms to enhance MSME tax compliance in the digital era.